Effects of personalized live-remote exercise for individuals living beyond primary curative cancer treatment: study protocol for a multinational, super umbrella randomized controlled trial (LION-RCT) - Hiensch, Anouk; Müller, Jana; Zopf, Eva M.; Schmidt, Martina; Monninkhof, Evelyn M.; Trevaskis, Mark; Belloso, Jon; Clauss, Dorothea; Gunasekara, Nadira; Joaquim, Ana; Viamonte, Sofia; Schumann, Moritz; et al. (Trials, 2025)
Exercise is an effective strategy to reduce cancer- and treatment-related side effects and improve quality of life (QoL). Larger exercise effects are observed in cancer survivors with a higher symptom burden and when exercise interventions are supervised. Most studies conducted to date have not screened for symptoms at baseline and tailored the exercise intervention accordingly. Additionally, time and travel distance are common barriers to participation in supervised in-person exercise programs. Live-remote exercise, where exercise sessions are supervised by an exercise professional via a videoconferencing platform, might help overcome these barriers. Here, we describe the design of the LION randomized controlled trial (RCT). This RCT aims to assess the (cost-)effectiveness of side effect-targeted, live-remote exercise on QoL and the participants’ most burdensome side effect—fatigue, emotional distress, low physical functioning, or chemotherapy-induced peripheral neuropathy (CIPN)—in individuals who have completed primary curative cancer treatment.